Xanthogranulomatous Adrenalitis: A Case Report and Literature Review - Dai, Xiang; Zhang, Yuanyuan; Du, Yiqing; Lai, Shicong; Wang, Gongwei; Yu, Luping; Zhang, Xiaopeng; Xu, Tao (Frontiers in Urology, 2022)
Xanthogranulomatous adrenalitis(XGA) is a rare inflammatory condition of adrenal glands, and it may be a result of a combination of chronic infection and local bleeding. We herein present an exceedingly rare suspicious functional case of xanthogranulomatous adrenalitis occurring in a 44-year-old Chinese female patient. With a history of intermittent superficial infection and high level of C-reactive protein for 6 months, she presented to the hospital without fever or flank pain. Magnetic resonance imaging revealed a 5-cm right adrenal mass, which showed equisigna on T1WI and slightly long signal or equisigna on T2WI. The patient’s postoperative basal serum rennin was decreased and aldosterone to renin ratio was raised. The adrenal mass was diagnosed as xanthogranulomatous adrenalitis after laparoscopic radical adrenalectomy, which was confirmed by histologic examination and immunohistochemical staining for CD68. One month after surgery, the patient’s serum renin and aldosterone to renin ratio dropped to normal level. Our case shows that xanthogranulomatous adrenalitis may resembles functional adrenal neoplasm laboratorically and radiologically. The most likely cause of xanthogranulomatous adrenalitis is chronic infection, especially Gram-positive coccus infection. Xanthogranulomatous adrenalitis should be considered when the clinical and radiological manifestations are not typical for other inflammatory disease or adrenal neoplasm.